The Influence of Tax Understanding and Tax Sanctions on Individual Taxpayer Compliance (Study at Chalidana Group Office) - Fajar Ramadhan Widiyanto; Alberta Esti Handayani (Dhana, 2025)
This study aims to analyze the influence of tax understanding and tax sanctions on individual taxpayer compliance at the Chalidana Group Office. This study has three main objectives: (1) to determine the influence of tax understanding on individual taxpayer compliance, (2) to evaluate the influence of tax sanctions on individual taxpayer compliance, and (3) to simultaneously test the influence of tax understanding and tax sanctions on individual taxpayer compliance. The research method used is quantitative analysis with multiple linear regression analysis tools. Data obtained from respondents are processed to obtain results that can provide valid and reliable conclusions. The results of this study are expected to provide academic contributions in the development of tax science, especially related to taxpayer compliance. In addition, the results of this study are expected to provide practical benefits for the Chalidana Group Office in improving taxpayer compliance through a better understanding of tax regulations and the application of effective sanctions. This study provides new insights in the field of tax accounting and can be a reference for further researchers who want to explore more deeply the factors that influence taxpayer compliance.